THE EFFECT OF VISUAL AESTHETIC EXPERIENCE ON PURCHASE INTENTION AT KAVLING DPR CAFÉ IN SIDOARJO - Orlin, Faadihilah Alodia; Danang Tandyonomanu (The Commercium, 2025)
This study aims to determine the effect of visual aesthetic experience on purchase intention at the DPR Kavling Café in Sidoarjo. This study uses a quantitative approach, the analysis uses statistics and is based on the philosophy of positivism. The research process is deductive, which is to answer the formulation of the problem using concepts or theories so that hypotheses can be formulated which are then tested and analyzed. The relationship between variables and the objects studied is more causal, so that in the study there are two variables, namely independent and dependent variables. The data collection technique uses a questionnaire distributed to 100 respondents, using Accidental Sampling which is one of the non-probability sampling techniques in this study. The assessment of the research instrument uses a Likert scale, where the smallest value is 1 and the largest is 5. The validity test uses Pearson Product Moment, and the reliability test uses Alpha Cronbach. So that the value is 0.891 with 24 valid items on variable X and the value is 0.659 with 9 valid items on variable Y. The study with these two variables uses simple linear regression analysis, and the results prove that the visual aesthetic experience has a significant effect on purchase intention, with a determination coefficient value of 0.101 or 10.1% and a significance level (sig. f) of 0.001. The majority of respondents rated "moderate", which means they considered that variable X had quite an effect on variable Y.